Press xenobiotic 3-chloroaniline disturbance favors deterministic assembly with a shift in function and structure of bacterial communities in sludge bioreactors - Santillan, Ezequiel (2022)
Disturbances are thought to affect community assembly mechanisms, which in turn shape community structure and the overall function of the ecosystem. Continuous (press) disturbances can drive ecosystems to alternate stable states of community function and structure, but their effects on assembly mechanisms are still largely unknown. Here, we tested the effect of a press xenobiotic disturbance on the function, structure, and assembly of bacterial communities within a wastewater treatment system. Two sets of four liter sequencing batch reactors were operated in triplicate with and without the addition of 3- chloroaniline for a period of 132 days, following 58 days of acclimation after inoculation with sludge from a full-scale treatment plant. The temporal dynamics of bacterial community structure were derived from 16S rRNA gene amplicon sequencing. Community function, structure, and assembly differed between press disturbed and undisturbed reactors. Temporal partitioning of assembly mechanisms via phylogenetic and taxonomic null modeling analyses revealed that the deterministic assembly prevailed for disturbed bioreactors, while the role of stochastic assembly was stronger for undisturbed reactors. Our findings are relevant because research spanning various disturbance types, environments, and spatiotemporal scales is needed for a comprehensive understanding of the effects of press disturbances on assembly mechanisms, structure, and function of microbial communities.